The Role of rs6152 Allele and Non-Genetic Factors in Androgenetic Alopecia: A Pilot Study in the Indonesian Local Population - Sidarta, Erick; Sari, Triyana; Nataprawira, Sari Mariyati Dewi; Andianto, Ivan Christian; Sajiwo, Damar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Androgenetic alopecia (AGA) is a common form of hair loss which inflicts progressive hair loss leading to various patterns. The cause of this disease is believed to be multifactorial, which is majorly attributed to genetic and non-genetic factors. This pilot study aimed to investigate the association of rs6152 allele, a SNP on AR gene, with AGA, as well as explore other contributing factors in the Indonesian local population. Methods: In this cross-sectional study, a total of 100 participants, which categorized into alopecia subjects and non-alopecia subjects, were enrolled for rs6152 SNPs detection. Anthropomorphic data such as height and weight, blood pressure and family history were obtained by measurement and questionnaire. Results: The study showed low frequency of individuals with rs6152 non-risk alleles (2%) and further analysis showed no significant association between rs6152 allele and AGA. However, familial history analysis revealed a strong association between family history and AGA risks. Additionally, age, gender, hypertension status and BMI were identified as significant factors associated (p-value < 0.05) with AGA. Conclusion: rs6152 was not a reliable genetic marker for AGA in the Indonesian local population. While familial history with AGA showed the inheritance pattern of autosomal dominant inheritance with sex limitation, non-genetic factors such as age, gender, hypertension status and BMI were strongly associated with AGA risk. This shows the complexity and multifactorial causes of AGA in the Indonesian local population.